2015
DOI: 10.1155/2015/307032
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Studies for Generic Omeprazole Magnesium Enteric Coated Tablets

Abstract: Preformulation is an important step in the rational formulation of an active pharmaceutical ingredient (API). Micromeritics properties: bulk density (BD) and tapped density (TD), compressibility index (Carr's index), Hauser's ratio (H), and sieve analysis were performed in order to determine the best excipients to be used in the formulation development of omeprazole magnesium enteric coated tablets. Results show that omeprazole magnesium has fair flow and compressibility properties (BD 0.4 g/mL, TD 0.485 g/mL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The drug was thoroughly mixed with excipients in a ratio of 1:1, and all the samples were stored at 40°C and 75% RH in closed vials for 21 days and then scanned by FTIR. The spectra of pure drugs and mixtures of drugs with excipients were compared with standards to check for any physical and chemical incompatibility 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…The drug was thoroughly mixed with excipients in a ratio of 1:1, and all the samples were stored at 40°C and 75% RH in closed vials for 21 days and then scanned by FTIR. The spectra of pure drugs and mixtures of drugs with excipients were compared with standards to check for any physical and chemical incompatibility 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…During the compounding of the tablet, the compatibility of the excipients with the API needs to be carefully considered. Migoha et al [ 263 ] showed that omeprazole can interact with components of the tablet mass. In preformulation studies, they observed that omeprazole interacted with Aerosil 200 (colloidal silica), turning dark purple or dark brown, depending on the test conditions.…”
Section: Development Of New Formulations With Ppismentioning
confidence: 99%
“…In preformulation studies, they observed that omeprazole interacted with Aerosil 200 (colloidal silica), turning dark purple or dark brown, depending on the test conditions. For other excipients, such as sodium lauryl sulfate, Avicel PH 101, magnesium stearate, lactose, and starch, no change was identified [ 263 ].…”
Section: Development Of New Formulations With Ppismentioning
confidence: 99%
“…Briefly, 10 mg drug was mixed with 20 ml of octanol and water in a separating funnel and shaken for about half an hour. The separating funnel was kept for 24 h and concentration of solute was measured in each solvent using UVspectrophotometer (UV 3000+, Lab India Instruments, Mumbai, India) at 290 nm [11], [12] .…”
Section: Determination Of Partition Coefficientmentioning
confidence: 99%